Managing Aminotransferase Elevations in Patients with Friedreich Ataxia Treated with Omaveloxolone: A Review and Expert Opinion on Use Considerations - Susan Perlman; Mathieu Anheim; Sylvia Boesch; James H. Lewis; David R. Lynch (Neurology and Therapy)
Abstract Omaveloxolone is approved for the treatment of Friedreich ataxia (FA) in patients aged ≥ 16 years and is under clinical development for pediatric patients. In the MOXIe study, alanine and aspartate aminotransferase (ALT and AST) elevations were among the most common treatment-emergent adverse events (TEAEs) in the omaveloxolone arm and were mild to moderate, generally asymptomatic, transient, and reversible; no patients who received omaveloxolone had laboratory abnormalities that met the Hy’s law criteria. Omaveloxolone labels (US and EU) provide guidance for monitoring and managing these elevations. Here, practical use considerations, from experience-based opinions of four FA experts and a hepatologist via semi-structured interviews, are presented. Prior to omaveloxolone initiation, assessment of baseline ALT, AST, and total bilirubin is recommended per label. During treatment, ALT, AST, and total bilirubin should be monitored monthly for the first 3 months and periodically thereafter per label. Reduced frequency of patient monitoring after 3 months is suggested if aminotransferase levels remain normal. Per label, omaveloxolone should be temporarily discontinued if aminotransferases increase to > 5 × the upper limit of normal (ULN) or > 3 × ULN with other evidence of liver dysfunction. Stemming from real-world practical considerations wherein patients are followed up less frequently than in the trial setting, treatment interruption when aminotransferases increase to ≥ 3 × ULN without other signs of hepatic impairment may be considered. When aminotransferase elevations stabilize or resolve, omaveloxolone may be reinitiated with an appropriate increased frequency of monitoring of liver function per label. We propose patients who pause treatment may have testing repeated after 2 weeks, while those with resolving aminotransferase elevations may reinitiate omaveloxolone with stepwise dose titrations and testing every 2 weeks for ≈ 3 months. Use considerations herein may inform decisions on monitoring and managing ALT and AST elevations, which potentially help to encourage the treatment adherence needed to achieve the slowing of FA progression seen in MOXIe. Graphical abstract available for this article. Graphical Abstract